INFLUENCE OF SIRE´S BREEDING VALUES AT MILK PRODUCTION AND REPRODUCTION OF DAIRY COWS - R KECLÍK; M ŠTÍPKOVÁ; J KUČEROVÁ; M MARŠÁLEK; J FRELICH (Journal of Central European Agriculture, 2002)
There was observed 621 of dairies of Bohemian Spotted Cattle. During the evaluation of milk production depending on level of sire´s breeding value for production of milk were found the values 5113,05 kg of milk, 180,06 kg and 3,51 % of protein at group of dairies at 1st lactation coming from testing breeding. Their milk production was about 13,82 kg of milk lower than by daughters of sires with the highest level of PH (+372,03 kg). There was found the best value of empty days (81,05 of day) at the group of dairies of sires with the lowest PH for amount of milk.